The effect of subjective norm, perceived control, attitude, and past experience on purchase intention of luxury clothes brands in Brazil - de Araújo, C.; Loureiro, S. M. C. (Tourism and Management Studies, 2014)
The main goal of this study is to extend the theory of planned behaviour by introducing past experiences as antecedents of behavioural intentions and to test this model in the context of luxury consumption. In this vein, the Brazilian luxury market, more specifically in the São Paulo area, was selected due to its growing presence on the world stage of luxury products. Therefore, an online questionnaire was constructed based on a literature review, and data were collected. The findings suggest that attitude and perceived behaviour control are more important to explain word-of-mouth, whereas past experience, perceived behavioural control and subjective norms significantly impact willingness to pay more. The consumers most willing to pay more for a luxury brand are also more willing to continue to buy such brands in the near future.